Impact of passenger car NOx emissions and NO2 fractions on urban NO2 pollution – Scenario analysis for the city of Antwerp, Belgium. (February 2016) - Degraeuwe, Bart; Thunis, Philippe; Clappier, Alain; Weiss, Martin; Lefebvre, Wouter; Janssen, Stijn; Vranckx, Stijn
Abstract: The annual NO2 concentrations in many European cities exceed the established air quality standard. This situation is mainly caused by Diesel cars whose NOx emissions are higher on the road than during type approval in the laboratory. Moreover, the fraction of NO2 in the NOx emissions of modern diesel cars appears to have increased as compared to previous models. In this paper, we assess 1) to which level the distance-specific NOx emissions of Diesel cars should be reduced to meet established air quality standards and 2) if it would be useful to introduce a complementary NO2 emissions limit. We develop a NO2 pollution model that accounts in an analysis of 9 emission scenarios for changes in both, the urban background NO2 concentrations and the local NO2 emissions at street level. We apply this model to the city of Antwerp, Belgium. The results suggest that a reduction in NOx emissions decreases the regional and urban NO2 background concentration; high NO2 fractions increase the ambient NO2 concentrations only in close spatial proximity to the emission source. In a busy access road to the city centre, the average NO2 concentration can be reduced by 23% if Diesel cars emitted 0.35 g NOx /km instead of the current 0.62 g NOx /km. Reductions of 45% are possible if the NOX emissions of Diesel cars decreased to the level of gasoline cars (0.03 g NOx /km). Our findings suggest that the Real-Driving Emissions (RDE) test procedure can solve the problem of NO2 exceedances in cities if it reduced the on-road NOx emissions of diesel cars to the permissible limit of 0.08 g/km. The implementation of a complementary NO2 emissions limit may then become superfluous. If Diesel cars continue to exceed by several factors their NOx emissions limit on the road, a shift of the vehicle fleet to gasoline cars may be necessary to solve persisting air quality problems. Highlights: We model street canyon NO2 for different diesel car NOx emissions and NO2 fractions. We consider the changes in European, regional and local street canyon emissions. Air quality would benefit from compliance of diesel cars with Euro 6 under real-driving conditions. High NO2 fractions impact the exceedance of the hourly limit value of 200 μg/m 3 .